Giant paratubaric cysts - Ochoa, Edgar S. S; Rocha, Alfredo L.; Sanchez, Edilia A. (International Journal of Research in Medical Sciences, 2021)
Giant paratubaric cysts are mostly benign tumors, with incidence of 10%. The incidence rate of these neoplasms is 2% to 3% including cystitis, papillary carcinoma and serous papillary neoplasms, the course of disease begins with abdominal pain or increase in size of lower hemi abdomen, becoming complicated in approximately 3% of cases. The diagnosis is made with transabdominal or transvaginal ultrasound, abdominal and pelvis tomography or magnetic resonance. The treatment of small cysts is expectant and the large size is surgical way. We present the case of a 35-year-old woman who began her current condition three years after her pregnancy, with urination urgency, abdominal pain and sensation of abdominal mass, who was diagnosed and protocolized in a public second level hospital in Mexico City, treated with opened surgery, and good postoperative evolution.